CO2 reduction with Re(i)–NHC compounds: driving selective catalysis with a silicon nanowire photoelectrode. Issue 99 (22nd November 2016) - Jin, Tong; He, Da; Li, Wei; Stanton, Charles J.; Pantovich, Sebastian A.; Majetich, George F.; Schaefer, Henry F.; Agarwal, Jay; Wang, Dunwei; Li, Gonghu
Abstract : Excellent selectivity was observed in CO2 reduction using Re(i )–NHC catalysts on a silicon nanowire photoelectrode. Abstract : The CO2 -reduction activity of two Re(i )–NHC complexes is investigated employing a silicon nanowire photoelectrode to drive catalysis. Photovoltages greater than 440 mV are observed along with excellent selectivity towards CO over H2 formation. The observed selectivity towards CO production correlates with strong adsorption of the catalysts on the photoelectrode surface.